When sling operation may make urinary incontinence worse? - Rogowski, Artur; Baranowski, Włodzimierz (Menopause Review/Przegląd Menopauzalny, 2011)
Efficiency condition of sling operations is maintained urethral mobility. For exceeded urethral mobility evaluation Q-tip test may be used. Urethral hypomobility may be risk factor for lack of improvement after sling operations. Analysis of urodynamic parameters provides additional informations which may be useful for sling operations efficiency. As the potential markers of sling operations efficiency intrinsic sphincter deficiency (ISD), decreased detrusor contractility, decreased maximum cystometric bladder capacity below 200 ml and subvesical obstacle symptoms are mentioned among others. Sling operation failure may be result of improper operation technique, although this procedure has short learning curve. Contraindications for sling operations are among others: symptoms of overactive bladder – OAB or mixed urinary incontinence with increased urge incontinence compound. In patients with mixed urinary incontinence symptoms sling procedure using transobturator approach seems to be a better therapeutic option. However tension-free vaginal tape procedure may be more efficient in case of ISD in obese women and patients after operation treatment for stress urinary incontinence.